ANALISIS METODE DAN PERGESERAN PENERJEMAHAN PADA BAGIAN AKHIR AKTA NOTARIS - Salsabila, Lingga Hasna (Kementerian Sekretariat Negara Republik Indonesia, 2025)
A notarial deed is an example of a private legal text which requires a different approach in translation in terms of meaning accuracy, message faithfulness, and language style. As the world becomes increasingly globalized, the translation of notarial acts from Indonesian into English has become even more important. The purpose of this research is to analyze the translation methods and translation shifts applied to the final section of Notarial Deed. This research uses a qualitative method, adopting Newmark’s (1988) translation method framework and Catford’s (1965) theory of translation shifts. The data were collected from private notarial deed documents, focusing on translated version of the final sections. The analysis of translation methods and shifts on the final sections of the seventeen notarial deeds reveals the use of following translation methods: (1) faithful translation in eleven findings, (2) idiomatic translation in five findings, and (3) literal translation in five findings. Meanwhile, the translation shifts identified in the same data are: (1) structure shift in twelve findings, (2) unit shift in ten findings, (3) intra-system shift in five findings, and (4) level shift in two findings.